An assessment of the impact of banking reforms on economic growth and bank performance in Nigeria - Matthew O. Gidigbi (CBN Journal of Applied Statistics, 2017)
This study assesses the impact of banking reforms on banks' performance and economic growth for the period 1981 to 2015 by fitting an ANOVA model into Stepwise Regression. Using dummy variables to isolate reform periods, results show that banking reforms contribute positively to economic growth, especially in the period 1999 to 2004. Also, banking reforms are found to contribute negatively to banks' performance, following the 1993 reforms. The study confirms that banking system reforms in Nigeria have dual impact on the economy and banks' performance. The banking reforms are capable of promoting growth in the economy. Thus, the study recommends pre-crisis reforms testing by the apex bank.
Keywords: C22; C25; C32; E58; G21; O23; 330; ANOVA; Banking System; Economic Growth; Time Series Models